Post-acute management of the acquired long QT syndrome. Issue 1064 (2nd April 2014) - Barra, Sérgio; Agarwal, Sharad; Begley, David; Providência, Rui
Abstract: The mechanisms underlying drug induced QT prolongation and the immediate treatment of torsade de pointes have been extensively studied but the post-acute management of the Acquired Long QT Syndrome (ALQTS) remains to be addressed. We aimed to review the state of the art data regarding risk stratification, arrhythmic prevention and treatment of patients with ALQTS. A comprehensive review of the scientific data collectable from MEDLINE, EMBASE and COCHRANE (from inception to April 2013) was performed, and descriptive and qualitative information was extracted from the most relevant manuscripts. QT prolonging drugs are widely used in hospital clinical practice, and several studies have shown a high prevalence of QT interval prolongation in patients admitted to hospital and a high rate of prescription of QT interval prolonging drugs to patients presenting with QT interval prolongation. Therefore, the acute and post-acute management of ALQTS is of the utmost importance. Avoidance of offending triggers, electrocardiographic screening, pacing at a relatively fast lower rate limit and using pause prevention programming (preferably with concomitant β blocker treatment), implantable defibrillators in the highest risk patients, genetic testing and counselling in selected cases, and family screening are among the potentially applicable strategies. The latter is justifiable by the fact that some studies unveiled a surprisingly similar positive mutation rate in drug induced LQTS compared with congenital LQTS, supporting the hypothesis that the former can be regarded as a latent form of the latter. Drug challenge with D, L-sotalol in suspected LQTS and treatment with a carvedilol analogue, verapamil or an Ikr activating drug are still in need of further investigation. The post-acute management of patients with ALQTS has received scarce attention in the past, probably due to the fact that it is considered a reversible phenomenon in most cases. Considering the relatively high risk of arrhythmic recurrence in the highest risk ALQTS patients, effective preventive and treatment strategies are warranted, and further research is needed.